(untitled) (Baghdad Science Journal, 2019)
In this paper, we introduce the notions of Complete Pseudo Ideal, K-pseudo Ideal, Complete K-pseudo Ideal in pseudo Q-algebra. Also, we give some theorems and relationships among them are debated.